Exploration, Isolation, and Identification of Carotenoid from Bacterial Symbiont of Sponge Callyspongia vaginalis - Iqna Kamila Abfa; Ocky Karna Radjasa; A B Susanto; Handung Nuryadi; Ferry F. Karwur (Marine Science Department Diponegoro University, 2017)
During the past two decades research on marine bacteria has highlighted the tremendous potential of symbiotic-microorganisms as a source of bioactive secondary. One of the potential of the bacterial symbionts is producing a natural pigment, and these organisms can be used as a sustainable source of natural pigments. Carotenoid is one of the most important pigments that has important roles in physiological and molecular processes of microorganisms, as well as for human health. The objective of this study is to analyze carotenoid pigments from marine bacterial symbionts from sponge and to identify bacterial symbionts that produce carotenoid pigments. Pigment analysis was performed by a UV-VIS spectrophotometer and High Performance Liquid Chromatography (HPLC). Molecular bacterial identification was performed based on 16S rDNA sequence. The isolation of bacterial symbionts from C. vaginalison Zobell 2216E medium resulted in one bacterium, CB-SP5, positively synthesized carotenoids. By reverse phase HPLC analysis, the carotenoid pigments in the bacterial symbionts were identified as diadinoxanthin, fucoxanthin, neoxanthin, dinoxanthin, anddiadinochrome. CB-SP5 shared the highest level of 16S rDNA gene sequence similarity with Psychrobacter celer (99%). Keywords : carotenoid, sponge, bacterial symbiont, 16S rDNA.